The Inconsolable Memories. On Commemorating Practices in Serbia and Croatia (Jasenovac, Bleiburg, Belgrade’s Sajmište) - Giergiel, Sabina (Porównania, 2016)
The paper focuses on the national identity transformations in the two post Yugoslavian states, i.e. Serbia and Croatia. (Re) constructions of the past that have been taking place there since the 1990s mainly assume rejecting the common legacy based on the mythological guerilla fight, and then choosing those past events about which memories ought to be retained. The struggle of the adversative pasts (Serbian and Croatian), as well as the polarization of the Croatian society are demonstrated on the example of the commemorative practices connected to the memorial sites from the World War II (Jasenovac and Bleiburg). The paper also alludes to the site associated with Holocaust which might become the symbol of the universal, “reconciled” memory.